Aplikasi Rumah Pintar bagi Pemantauan dan Pengawalan Elektrik - Mohd Sazlan, Aina Sakinah; Mohd Yunus, Mohd Amin (Applied Information Technology And Computer Science, 2021)
Development of IoT in the industry has gained attention among the community in Malaysia and the most commonly used IoT applications is Smart Home. Smart Home is an application that controls the electrical devices such as lights and fans by using a smartphone or computer. Therefore, the Smart Home Application is developed for electrical control and monitoring at home. Normally, the process of open and close the electrical switch is by manual. Sometimes when user felt tired or forgot to turn off the switch and just leave it on has caused a waste of electrical energy. Therefore, the purpose of the application development is to help users control their electronic appliances even if they are away from home by using Android application. Smart Home Application was developed by using the Android operating system along with the ESP8266 microcontroller, Arduino and Current Sensor. ESP8266 have a Wi-Fi module that can interact with relay switches using the internet. Arduino IDE is used to program the electronic devices into the microcontroller, while the current sensor is to detect the electrical current in the wire. The application displays the switch controls and user information that will then be saved to a database, Firebase Firestore. With this application, users can manage electricity consumption at any time.